Study on Numerical Simulation of Influence of Sea Mud Resistivity on the Cathodic Protection Effect for Steel Pipe Pile - FANG Xiang, ZHANG Dong - fang, FAN Zhi - hong, XIONG Jian - bo (Cailiao Baohu)
Steel pipe piles in marine engineering are facing severe corrosive problems. Sacrificial anode cathodic protection is an effective way to protect steel pipe piles from corrosion. As for the previous cathodic protection design of steel pipe piles, the uneven layout of anodes and the influence of sea mud resistivity on the protection effect were not considered. Hence, with using numerical simulation methods, the dynamic studies were carried out on the change of cathodic protection effect as anode dissolved during the protection period. Results showed that due to the anodes distributed only in immersed zone, the protection effect of steel pipe pile under the buried zone was relatively poorer, and the pile tip was easier to be underprotected. Sea mud resistivity had a certain influence on the protection effect of steel pipe pile under the buried zone. Under the same cathodic protection design, steel pile pipe in sea mud with high resistivity was easier to be underprotected. In addition, the underprotected area started from the pipe tip and developed upwards.